Advancing African agency in the new 2030 transformative development agenda. Issue 1 (2nd January 2017) - Besada, Hany; Xu, Jiajun; Mathers, Annalise; Carey, Richard
Abstract : This paper explores the current transition from the MDG framework to the Sustainable Development Goal (SDG) framework in the post-2015 development agenda, with specific emphasis on how the SDGs with their aim of 'Transforming our World' might guide economic development and policy in Africa. The aim is to investigate the scope and implications of the post-MDG Agenda for Africa against the background of distinct disparities in development progress across the African continent, rapid urbanization, the availability of new technologies, and the emergence of parallel comprehensive new frameworks for managing global climate change and for creating synergies between China's transformation over the coming decades and Africa's Agenda 2063. Drawing on the changing shape of development finance and new insights into the role of public entrepreneurship for development, we make proposals for advancing African agency in the context of these new frameworks, and conclude with policy recommendations for the future.